Ulasan buku Dr Farish A. Noor - Amir, A.N.; Yoginder, S.; Farish, A.N. (Malaysian Sociological Research Institute (MSRI), Kuala Lumpur, 2004)
Islam Embedded—The Historical Development of the Pan-Malaysian Islamic Party PAS (1951-2003)